2018
DOI: 10.3390/ijms19103070
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans Are Attractive Biomarkers and Therapeutic Targets in Hepatocellular Carcinoma

Abstract: Proteoglycans, which consist of a protein core and glycosaminoglycan chains, are major components of the extracellular matrix and play physiological roles in maintaining tissue homeostasis. In the carcinogenic tissue microenvironment, proteoglycan expression changes dramatically. Altered proteoglycan expression on tumor and stromal cells affects cancer cell signaling pathways, which alters growth, migration, and angiogenesis and could facilitate tumorigenesis. This dysregulation of proteoglycans has been impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 130 publications
(136 reference statements)
2
38
0
Order By: Relevance
“…A growing body of literature describes potential predictive and prognostic biomarkers that may inform diagnosis and treatment of HCC. For early detection and/or diagnosis of HCC, oncofetal antigens, proteoglycans, enzymes and isoenzymes, such as the fucosylated fraction of AFP (AFP‐L3), des‐gamma carboxyprothrombin (DCP; also known as prothrombin induced by vitamin K absence or antagonism II), versican and glypican 3, have been evaluated . Clinical features related to tumour stage and treatment have also been characterized, including Barcelona Clinic Liver Cancer (BCLC) stage and macroscopic vascular invasion.…”
Section: Biomarkers In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature describes potential predictive and prognostic biomarkers that may inform diagnosis and treatment of HCC. For early detection and/or diagnosis of HCC, oncofetal antigens, proteoglycans, enzymes and isoenzymes, such as the fucosylated fraction of AFP (AFP‐L3), des‐gamma carboxyprothrombin (DCP; also known as prothrombin induced by vitamin K absence or antagonism II), versican and glypican 3, have been evaluated . Clinical features related to tumour stage and treatment have also been characterized, including Barcelona Clinic Liver Cancer (BCLC) stage and macroscopic vascular invasion.…”
Section: Biomarkers In Hccmentioning
confidence: 99%
“…Likewise, low neutrophil to lymphocyte ratio, aetiology, extrahepatic spread, high s‐c‐KIT, low baseline hepatocyte growth factor concentration, FGF3/FGF4 amplification and rare vascular endothelial growth factor‐A (VEGF‐A) amplification have also been associated with improved response to sorafenib . Conversely, elevated expression of VEGF‐A, K19, CD133, epithelial cell adhesion molecule (EpCAM) or serglycin as well as single nucleotide polymorphisms and angiopoietin‐2 levels in patients receiving sorafenib have been associated with poor prognosis . An exploratory analysis of the RESORCE trial suggests that decreased expression of lectin‐like oxidized LDL receptor 1, Ang1, cystatin‐B, latency‐associated peptide TGF‐β1 or macrophage inflammatory protein 1α may be predictive of the OS and time to progression treatment benefit observed from regorafenib, but these findings require prospective studies to confirm .…”
Section: Biomarkers In Hccmentioning
confidence: 99%
“…We previously reported that serum decorin levels are positively correlated with skeletal muscle mass in patients with HCC [16]. Decorin is also reported to interact with transforming growth factor-β and receptors of tyrosine kinase such as epidermal and insulin-like growth factors [17], leading to suppression of proliferation of various tumor cell lines, including HCC cell lines [18][19][20]. In addition, decorin is known to be expressed in various tissues including intestinal tissue, cardiac tissue, and adipose tissue and is known to regulate autophagy, inflammation, and glucose homeostasis [21][22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, inhibitors of glycosaminoglycan biosynthesis may affect liver metastasis potential of tumor cells [45]. The proteoglycan composed of protein core and glycosaminoglycan chain plays a vital role in the development of HCC, and is been explored as a potential HCC biomarker and therapeutic target [46]. Glycosaminoglycans are involved in HA synthesis, and Stabilin-2 as the main scavenger receptor for systemic HA [47], is involved in regulating HA metabolic pathways as reported previously.…”
Section: Discussionmentioning
confidence: 75%